Cascaded dual-tapered optical microfiber sensors for simultaneous detection of refractive indices in multiple solutions - Zulkeflee, Nurul Nadiah; Kamil, Yasmin Mustapha; Abu Bakar, Muhammad Hafiz; Mashohor, Syamsiah (Taylor and Francis, 2024)
A cascaded single-mode tapered fiber (SMTF) has been investigated for simultaneous detection of two refractive indices (RI). Two SMTFs with distinct-free spectral range (FSR) of 3.88 nm and 23.23 nm were concatenated to realize the cascaded SMTF. The interaction between evanescent waves generated by the cascaded SMTF and variations in the surrounding environment results in measurable wavelength shifts. When tested with different concentrations of sodium chloride to simulate RI variations, wavelength shifts were yielded with FSR corresponding to the stimulated SMTF. This work validates the feasibility of using cascaded SMTFs for simultaneous dual RI detection in real-world applications.